2019
DOI: 10.1007/s11306-019-1560-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of childhood exposure to perfluoroalkyl substances: a cross-sectional study

Abstract: JMB and KDP conceived the study. AC, JMB, and YX led and supported the HOME Study and YX provided all HOME Study data. AMC measured serum PFOA concentrations. DIW, DPJ, and KDP provided metabolomics expertise and high-resolution metabolomic profiling of serum samples. SLK performed all statistical analyses with guidance from GDP and DIW. SLK drafted the manuscript, tables, and supplemental material. DIW also contributed to manuscript writing. All authors reviewed, edited, and approved the final manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…(Wang, X. et al 2017) Two studies in children also showed that PFAS levels in blood were associated with significant alterations in glycophospholipid metabolism and several amino acid pathways such as tyrosine, aspartate and asparagine. (Alderete et al 2019; Kingsley et al 2019)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wang, X. et al 2017) Two studies in children also showed that PFAS levels in blood were associated with significant alterations in glycophospholipid metabolism and several amino acid pathways such as tyrosine, aspartate and asparagine. (Alderete et al 2019; Kingsley et al 2019)…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated reference standardization provides estimates of concentrations consistent with both endogenous and exogenous compounds,(Accardi et al 2016; Go et al 2015a; Walker et al 2019) and high-correlation with PFAS measurements by validated, targeted approaches. (Kingsley et al 2019)…”
Section: Methodsmentioning
confidence: 99%
“…PFASs, on the other hand, are a group of man-made chemicals that have been widely used since the 1950s in both household and industrial products. PFASs also have long biological half-lives, and are readily detected in humans [3][4][5][6][7]. Structurally, several PFAS compounds resemble endogenous fatty acids, with fluorine substitution in place of hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we are able to derive sleep measures from the actigraphy data. 55 56 Other biomarkers We measured other biomarkers including leucocyte DNA methylation, 57 high-resolution metabolomics, 58 gonadal hormone concentrations and vitamin D metabolite concentrations. We also conducted a drug screen on children's urine using a clinical drug panel assay.…”
Section: Physical Activity Diet and Sleepmentioning
confidence: 99%